النصوص الشعرية في مقرَّر لُغتي للمرحلة الأولية في المملكة العربية السعودية- دراسة لغوية للعام الدراسي 2023-2024م: Poetic Texts in ‘My Language’ Course for the Primary School in the Kingdom of Saudi Arabia - A Linguistic Study for the Academic Year 2023-2024 - Badr Alhussein, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يُلقي هذا البحث الضوء على النصوص الشعرية في مُقرَّر اللغة العربية (لغتي) للصفوف الأولية في المملكة العربية السعودية للعام الدراسي 2023-2024، ويدرسُها من النَّاحية اللغوية. سيأتي البحث على دراسة النصوص الشعرية من حيث التراكيب اللغوية والألفاظ والأوزان الشعرية ومدى مناسبتها للمرحلة العُمريَّة من (6-8) سنوات، مع اقتراح بدائل للألفاظ التي يصعُب فهمُها على التلاميذ، وكذلك تقديم اقتراحات لغوية وفنية لتستقيمَ الأوزان الشعرية لهذه النصوص. ويبيِّن البحث أهمية الأناشيد في مسيرة التعلُّم للتلاميذ في هذه المرحلة العمرية المهمة؛ حيث يُؤمَّل منها أن تُثريَ لُغتهم، وتساعدَهم على تذوُّقِ الشعر العربيّ، ومحاكاةِ تراكيبه المميَّزة. ويوضِّحُ هذا البحث مدى اشتمال النصوص الشعرية في مقرَّر لغتي للمرحلة الأولية على جوانب الحياة التي يعيشُها التلاميذ بما يقع في دوائر اهتماماتهم. ويُعنى البحث كذلك برصد المضامين والأفكار التي تطرَّقت لها النصوص الشعرية في المقرَّرات المذكورة، وتقديم اقتراحات من أجل إدراج موضوعات لم تتطرَّق لها المقرَّرات المذكورة، وبيان أهمية إدراجها. ABSTRACT This research sheds light on the poetry (rhymes) selected for the Arabic Language Curriculum (LOGHATY), taught across the lower elementary school grades in the Kingdom of Saudi Arabia (2023-2024). It also provides a linguistic analysis of the sampled rhymes. The research offers a linguistic study of the sampled rhymes in terms of word-choice appropriacy, age, clarity, easiness, musicality, rhythmicality, prosody, flow, and other considerations for childhood to generate a positive impact on the mind and heart. Alternatives are occasionally suggested for some words to create a better rhyming flow for pupils when difficult words make it difficult for them to chant out such rhymes while still aged 6-8. In addition, the research reveals the importance of school rhymes in pupils' learning journey at this critically important age. These rhymes are expected to enrich their language, help them taste Arab poetry, and simulate its distinctive phrases. This research illustrates the extent to which the rhymes in question encompass aspects of these pupils' lives of concern. Equally important, the research also flags up some topics, implications, and pieces of knowledge left unnoticed by the curriculum that needs to be well addressed and officially included as core thematic components to better achieve the objectives set.